(untitled) (LACCEI, 2024)
In the present research work, the evaluation of the quality of the compost obtained from organic waste in the city of Lima-2022 was carried out. The problem lies in the mismanagement of solid waste by street vendors, merchants and civilians. This generates waste such as fruit peels, sawdust, sheep feces, among others. Bringing as consequences a direct impact to the ground, in addition to possible sources of health risk. The design of a compost bin was carried out taking into account the methodology used in the research project Preparation of compost from the organic waste generated in the cleaning of the plant of the company COPEINCA SAC Finally the sample was taken to the accredited laboratory System of services and chemical analysis S.A.C (SLAB), obtaining a quality compost within the parameters provided by the WHO and the comparison with the Chilean regulation 2880 was also made.